Students Error Analysis in Descriptive Text of UNCP - Juwita Crestiani M; Opik Dwi Indah; Hermini Hermini; Muhammad Hasby (Institut Agama Islam Negeri Palopo, 2024)
This research deals with the the kinds of errors of the first semester students of Elementary School Teacher Education Study Program of Palopo Cokroaminoto University mostly do in their writing. The population of this research is the first semester students of Elementary School Teacher Education Study Program of Palopo Cokroaminoto University in academic year 2023. The total number of population was 200 students. The researcher applied the purposive sampling technique and there are 20 students as sample. Writing test is the instrument of this research. Based on the findings and discussion in the previous chapter, the researcher concludes the kinds of errors of the first semester students of Elementary School Teacher Education Study Program of Palopo Cokroaminoto University mostly do in their writing is selection. It can be proven by the kinds of error made by the students are selection error (21 errors or 53.84%), omission error (9 errors or 23.07%), and addition error (9 errors or 23.07%).